1979
DOI: 10.5479/si.00810282.301
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the pentadactylus species group of the frog genus Leptodactylus (Amphibia, Leptodactylidae

Abstract: and pattern characters are analyzed for the adult members of the Leptodactylus pentadactylus species group. Available data on tadpoles, mating calls, and karyotypes are incorporated in the analyses. Results of the analyses lead to the recognition of 11 species comprising the group. For each species, the following are provided: synonymy, description of adult characteristics, a distribution map and list of localities, and specimens examined. The following are included if known: distinctive adult colors in life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
230
2
27

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(266 citation statements)
references
References 7 publications
7
230
2
27
Order By: Relevance
“…Both species are stocky and short legged. In the previous study (Heyer 1978), L. bufonius demonstrated sexual dimorphism in SVL (females larger), head length (male heads longer), head width (male heads wider), whereas L. troglodytes demonstrated sexual dimorphism in head length (male heads longer), shank length (male shanks longer), and foot length (male feet longer). In this study, both L. bufonius and L. troglodytes demonstrate statistically significant differences in femalemale SVL, but SVL differences are considered not meaningful and can not be demonstrated to be dimorphic for L. troglodytes with the available data.…”
Section: Comparison With Previously Published Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both species are stocky and short legged. In the previous study (Heyer 1978), L. bufonius demonstrated sexual dimorphism in SVL (females larger), head length (male heads longer), head width (male heads wider), whereas L. troglodytes demonstrated sexual dimorphism in head length (male heads longer), shank length (male shanks longer), and foot length (male feet longer). In this study, both L. bufonius and L. troglodytes demonstrate statistically significant differences in femalemale SVL, but SVL differences are considered not meaningful and can not be demonstrated to be dimorphic for L. troglodytes with the available data.…”
Section: Comparison With Previously Published Resultsmentioning
confidence: 99%
“…In a previous study (Heyer 1978), L. furnarius (as L. laurae) demonstrated sexual dimorphism in SVL (females larger) and no dimorphism in thigh, shank, or foot length; L. gracilis demonstrated dimorphism only for head width (male heads longer) for the variables analyzed. Our results demonstrate statistically significant results solely for SVL in L. furnarius (females larger), with an effect size of 0.385, a medium effect size as defined herein.…”
Section: Comparison With Previously Published Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two sources of information have been most critical in reassessing species limits in frogs: molecular and advertisement call data. For example, Toda et al (1998) concluded that genetic divergences within Rana limnocharis were of such a magnitude that several morphologically indistinguishable species were 40 W. RONALD HEYER and YANA R. REID sidered to be a single species based on morphological and limited advertisement call data (Heyer 1978) with a distribution ranging from Panama and Colombia east of the Andes to Argentina and on the islands of Margarita, Trinidad, and Tobago. A more recent molecular study estimated genetic differentiation in the species from throughout its geographic range and demonstrated lack of genetic cohesion to such a degree that L. fuscus likely is composed of several species (Wynn and Heyer 2001).…”
Section: Introductionmentioning
confidence: 99%